Cover feature: Analyte focusing by micelle collapse for liquid extraction surface analysis coupled with capillary electrophoresis of neutral analytes on a solid surface. Issue 18 (2nd September 2019) - Jeong, Sunkyung; Shakerian, Farid; Chung, Doo Soo
Abstract : DOI:10.1002/elps.201900113 The cover picture shows (1) liquid extraction surface analysis (LESA) coupled with (2) capillary electrophoresis (CE) using a commercial instrument in an automatic manner. A solid surface sample (apple skin with water‐insoluble neutral pesticide residues) is directly sampled by forming a liquid microjunction containing sodium dodecyl sulfate micelles between the surface and the capillary inlet. Thus, unnecessary dilution from bulk sampling is avoided and the extraction of the neutral compounds is enhanced by the micelles. The extracts can be further enriched through analyte focusing by micelle collapse, a sample preconcentration technique applicable to neutrals, before CE analysis.